Notas sobre una mirada inclusiva para el estudio de las relaciones internacionales - Morales Barckhahn, Ignacio (Revista Inclusiones, 2021)
This article aims to present some ideas that attempt to reinforce what we understand as an inclusive understanding for the theoretical and practical study of international relations. With examples related to the study of contemporary arab world, we will try to present some considerations to provide new perspectives to the academic development related to the study of international conflicts and their respective actors.